Cognitive Linguistics and the Poetics of Time: Is 9/11 a Conceptual Metaphor, a Conceptual Metonymy or Both? - Adán Martín; Juani Guerra (Miscelánea: A Journal of English and American Studies, 2010)
Time has always hard-pressed the human symbolic capacity for language to an extent that few other concepts have. Equally, it has helped to linguistically shape human narrative imagination in a creative interaction with space that no other concept has known. In this paper, the argumentation concerns a very concrete piece of language which shows how human conceptual projections work to make new social structures of meaning emerge. We will explore the meaning-construction properties of a highly specific time lexicalisation which refers to a well-known terrorist attack: 9/11. We will consider why we employ this expression and which cognitive operations are involved in that peculiar conception of time and events.